The Association Between Energy Adequacy Level And Physical Activity With Nutri-tional Status In Adolescents At Walisongo High School, Ketanggungan - Nur Indah Dewi Rahmawati; Luluk Ria Rakhma (Eduvest - Journal of Universal Studies, 2024)
Growth during adolescence is rapid due to the development of muscle mass and fat tissue as well as hormonal changes that affect the nutritional needs of adolescents. The purpose of this study was to determine how the nutritional status of adolescents and the level of energy adequacy and physical activity relate to each other. This type of research uses a cross-sectional design. The number of samples taken with simple random sampling technique in this study was 152 people. Data collection of energy adequacy level using SQ-FFQ, physical activity data with PAL questionnaire, and nutritional status of respondents obtained from measurements of BW and TB. The results showed that most participants had an adequate level of energy sufficiency (65.1%) according to the Spearman Rank test, physical activity was mostly in the moderate category (63.8%), and the majority had good nutritional status (80.9%). The results of the Spearman Rank test showed that there was a significant correlation between the level of energy adequacy and nutritional status (p value = 0.045) and there was a significant correlation between physical activity and nutritional status (p value = 0.021). The conclusion is that there is a significant correlation between the level of energy adequacy and physical activity with nutritional status in adolescents at Walisongo Ketanggungan High School. It is recommended for the school to collaborate with the health department or local health center to make preventive and promotive efforts related to nutritional status problems through education about General Guidelines for Balanced Nutrition (PUGS).